KUALITAS JASA DAN KEPUASAN PELANGGAN DALAM PEMBELIAN ULANG PADA KELOMPOK KONSUMEN LANJUT USIA DI MATAHARI DEPARTMENT STORE SIDOARJO - Yusni Cahyo Nugroho; Tatik Suryani (Journal of Business & Banking, 2011)
This research analyzes the causal variables that influence the variables of service quality to satisfaction and repeat purchase intention at Matahari Department Store. The analyzed vari- able are user service quality (physical aspects, reliability, personal interaction, problem solving and policy), satisfaction and repeat purchase intention. The purpose this study is to identify grey consumers perceived service quality at Matahari department Store in Sidoarjo city and to examine the relationship among perceived service qualities, their satisfaction, and repeat purchase intention to that store. A structured questionnaire was developed to collect the data. Designs for sample in this study is non-probability sampling, with the techniques of analysis such as descriptive analysis and statistic analysis. A model confirmatory analysis factor (CFA) and structural equation modeling (SEM) built by using AMOS 16.0 for windows program. The result showed that all service quality dimensions in the study, except policy, were significantly and positively to have relationship with their satisfaction and repeat pur- chase intention at Matahari Department Store, Sidoarjo Finally, for the further studies that test the same model and with the same research design, the authors suggest that the number of sample is by taking bigger and broader area for collecting data.